Bamboo Dancing Method in Speaking Class for Eleventh Graders - Mujadid, Alief Jauhar; Ningrum, Ary Setya Budhi (Universitas Nusantara PGRI Kediri, 2022)
The goal of this study is to see how effective the Bamboo Dancing Method is for teaching speaking skills. This study is quasi-experimental in which students in class XI SMAN 2 Pare were the focuses of this investigation. Class XI MIA 1 was the experimental group, and class XI MIA 7 was the control group. Pre-test and post-test in the form of speaking tests are employed for collecting data. In analyzing the data, ANCOVA was used to calculate the results. In the pre-test findings, the average value of the experiment was 53.00, while the control group mean was 54.00. The average value for the experiment on the post-test was 77.00, while the mean score for the control group was 73.83. According to the statistical calculation findings of ANCOVA, the results were significantly high, .000 < .05. Since the significance value is less than 0.05, it suggests that there is sufficient evidence to reject the null hypothesis; hence the alternative hypothesis is accepted. This indicates that employing the Bamboo Dancing Method to develop speaking skills is efficient.